(untitled) (CIPEEX, 2025)
Advances in digital technologies have profoundly transformed electoral processes in Brazil and around the world. Social media plays a central role in political communication, influencing voter behavior and election outcomes. However, complex challenges have arisen, such as the spread of misinformation and the misuse of personal data, which require effective regulation in the digital environment.Studies show that each digital platform has its own engagement dynamics, favoring polarized discourse and hindering access to reliable information. The General Data Protection Law (LGPD) and the resolutions of the Superior Electoral Court (TSE) seek to ensure the integrity of the democratic process in the face of new virtual threats.Data from the DataSenado Institute confirm that misinformation is a real factor influencing elections, with a large portion of the population reporting frequent exposure to fake news. This work adopts a qualitative and exploratory approach, reviewing scientific articles, books, and academic studies published over the past ten years. Recent election campaigns were analyzed, with an emphasis on the 2018 and 2022 Brazilian elections, to understand how candidates used social media as tools for political communication. The study also considered the role of major digital platforms in disseminating messages and engaging with the electorate.The results show that social media has become central to election campaigns, allowing for greater visibility and direct engagement with voters. However, misinformation remains a major challenge, affecting public debate and intensifying political polarization. Combating misinformation is essential to ensuring informed choices and strengthening the democratic process in Brazil.